Communication Network Analysis K-Pop Fans Through the WhatsApp Group Application - Paramita, Sinta; Laila, Kumi (Jurnal Komunikasi, 2022)
Korea Pop (K-Pop) is a music industry originating in South Korea. Its existence is currently one of the largest music industries in the world. Talking about K-Pop is inseparable from the reality of its fans. The presence of passionate fans makes K-Pop even more popular. Fans have various ways to worship the idols they like, one of which is a shipper. Activities, issues, or rumors concerning their idols are always discussed by shippers through discussion rooms, such as the WhatsApp Group, to exchange opinions or equalize opinions. This study aims to find out what the mapping of the communication network structure looks like in a Jenlisa Universe WhatsApp Group. Jenlisa Universe is a shipper community that pairs Blackpink members Jennie and Lisa, known as Jenlisa, in a relationship. Shippers are K-Pop fans who pair their idols with other idols in a pairing relationship, which can be romantic, romantic, friendship, family, and emotional. They always connect the activities of each idol as if they have a relationship with one another. Currently, Jenlisa's shipper is included in the top 5 shippers worldwide. This is why Jenlisa's shipper was chosen as the subject of this study. The theory needed is an opinion leader, namely a figure or leader who influences a community. The approach in this study is descriptive quantitative. The method used is Communication Network Analysis with the Chat Stats WhatsApp Statistics application, Ucinet, and interviews conducted with participants in the group. The results of this study show that Jenlisa Universe, as a WhatsApp Fanbase Group, has 13 famous actors who act as opinion leaders who serve as discussion guides for rumors, cases, or Jenlisa activities in a WhatsApp Group network.